If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8-(-x+6)=-10-x
We move all terms to the left:
8-(-x+6)-(-10-x)=0
We add all the numbers together, and all the variables
-(-1x+6)-(-1x-10)+8=0
We get rid of parentheses
1x+1x-6+10+8=0
We add all the numbers together, and all the variables
2x+12=0
We move all terms containing x to the left, all other terms to the right
2x=-12
x=-12/2
x=-6
| 4n+3-7=16 | | 8x-2x-10=2x+6 | | -6y-y=12-16 | | X/20+x=6.25 | | 4x+3=12x+83 | | 1/8=s-3-4 | | -2.4+y/7=-19.9 | | Y=2x+10x+8 | | -(5+4x)=-5-3x | | 3(2x+5)=5x7 | | 4n+7=-25 | | 27y3=3y | | 10-4x=-6x=30 | | 34=-4(1-9f)-2 | | 9=(3/8)a | | 90+2x+3x-10=90 | | y/3+4.4=-3.1 | | (8(4w+7)/3=1 | | -5g+2.2=17.8 | | 13x-22(8+5x)=12-11x | | 12x-12=4x-20 | | 34=-4(9-f)-2 | | 0.5x-10=0.2x+4 | | 150+5x=130+3x | | 90+2x+3x-10=60 | | (2/(x+7))=3 | | 2y-3/5=12 | | 160.67=2000*r*8/12 | | (3x+4)=124 | | 12x-1=11x-2 | | 64=-8r | | 64=y4 |